Cutaneous manifestations associated with COVID-19: summary of current knowledge - Jung, Magdalena; Woźniak, Kinga; Jung, Maximilian; Sysło, Oliwia; Hedesz, Patryk; Gardian-Baj, Monika; Szczerbiak, Alicja; Jędral, Krystian; Żuk-Łapan, Aleksandra; Doryń, Aleksandra (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Coronavirus disease (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), had been spreading rapidly throughout the world, mainly affecting respiratory system. Except pulmonary symptoms, skin lesions might also occur. The precise percentage of patients with confirmed COVID-19 who presented cutaneous manifestations is still unknown (0.2% - 20.4%). Part of the skin lesions might be drug-induced. Brief description of the state of knowledge: Cutaneous manifestations in the course of the coronavirus disease could be divided into six main groups: maculopapular rash, urticarial lesions, chilblain‐like lesions, vesicular eruptions, petechial/purpuric lesions and livedoid lesions. The most common skin lesions are maculopapular eruptions (47%). Trunk is the most affected location, whereas pruritus is the most frequent additional symptom among patients with skin lesions associated with coronavirus disease. These lesions appear mainly in elderly patients except pseudo chilblains which are present among children and young adults with SARS-Cov-2 infection. The majority of cutaneous manifestations occur after COVID-19 systemic symptoms, but the appearance of vesicular lesions before the respiratory signs was also reported. Cutaneous manifestations resolved spontaneously at different times, ranging from a few days to 2-4 weeks. Moreover, patients with severe course of COVID-19 with maculopapular rash have better prognosis (2% mortality rate) in comparison to patients who developed livedoid lesions in course of the coronavirus disease (10% mortality rate). Summary: Pseudo-chilblains and vesicular lesions are the most specific cutaneous manifestations of coronavirus disease. Healthcare professionals should pay attention to patients who present skin symptoms in the course of COVID-19. Cutaneous manifestations can facilitate the doctor the diagnosis and even estimate the severity of coronavirus disease.